2000
DOI: 10.1021/bi0013039
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anticodon Architecture of Human tRNALys3 Includes Disruption of Intraloop Hydrogen Bonding by the Naturally Occurring Amino Acid Modification, t6A

Abstract: The structure of the human tRNA Lys3 anticodon stem and loop domain (ASL Lys3 ) provides evidence of the physicochemical contributions of N6-threonylcarbamoyladenosine (t 6 A 37 ) to tRNA Lys3 functions. The t 6 A 37 -modified anticodon stem and loop domain of tRNA Lys3 UUU (ASL Lys3 UUU -t 6 A 37 ) with a UUU anticodon is bound by the appropriately programmed ribosomes, but the unmodified ASL Lys3 UUU is not [Yarian, C., Marszalek, M., Sochacka, E., Malkiewicz, A., Guenther, R., Miskiewicz, A., and Agris, P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
127
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 50 publications
(117 reference statements)
6
127
0
2
Order By: Relevance
“…Comparing it with various hypomodified and unmodified analogs revealed opposing effects of the base modifications on ACNase reactivity. Correlating these data with the observed contributions of the base modifications to the ASL solution structure (12,14,15) leads us to suggest that ACNase prefers substrates where the anticodon nucleotides assume a stacked A-RNA conformation and where the base pairing interactions in the ASL stem are relatively destabilized. We also show that the PrrC D287H mutation renders human tRNA Lys3 relatively more reactive than the natural substrate.…”
Section: A Trnamentioning
confidence: 84%
See 2 more Smart Citations
“…Comparing it with various hypomodified and unmodified analogs revealed opposing effects of the base modifications on ACNase reactivity. Correlating these data with the observed contributions of the base modifications to the ASL solution structure (12,14,15) leads us to suggest that ACNase prefers substrates where the anticodon nucleotides assume a stacked A-RNA conformation and where the base pairing interactions in the ASL stem are relatively destabilized. We also show that the PrrC D287H mutation renders human tRNA Lys3 relatively more reactive than the natural substrate.…”
Section: A Trnamentioning
confidence: 84%
“…The wobble base side chain mnm 5 U34 also stabilizes the anticodon base stacking and U-turn conformation but partially counteracts the base pair disrupting effect of t 6 A37. Destabilization of the stem and/or the C 32 -A 38 base pair (21) by t 6 A37 also opposes the effect of the ⌿39 modification (12,14,15). Here we have shown that the ASL base modifications also exert distinct effects on ACNase reactivity (Tables I and II).…”
Section: The Trnamentioning
confidence: 99%
See 1 more Smart Citation
“…The bulky residue prevents the intraloop hydrogen bond between residues 32 and 37, thus promoting proper pre-structuring of the ASL. 116,117 In mitochondrial tRNAs, imG 37 or its derivatives are commonly replaced by i 6 A 37 or a derivative thereof, or by a methylated purine, therefore suggesting the evolution of an alternative strategy for establishing the same functional properties by using different chemical moieties in RNA modifications. 113,116 …”
Section: The Modified Wobble Hypothesis and Decoding At Position 34mentioning
confidence: 99%
“…Furthermore, in the absence of modifications, the U-rich ASL cannot effectively form stacking interactions to stabilize its structure nor negate intraloop hydrogen bonding that effectively condenses the size of the ASL. 117 The nearly ubiquitously modified, invariable purine at position 37 can alleviate the thermodynamic penalty of a pyrimidine rich anticodon. In tRNA Lys UUU the purine at position 37 is modified to N 6 -threonylcarbamoyladenosine, t 6 A or a derivative thereof such as 2-methylthio- N 6 -threonylcarbamoyladenosine, ms 2 t 6 A 37 found in mammalian tRNA Lys3 UUU .…”
Section: The Modified Wobble Hypothesis and Decoding At Position 34mentioning
confidence: 99%